Searching for trust : blockchain technology in an age of disinformation / Victoria L. Lemieux, University of British Columbia. - Lemieux, Victoria L., 1963- (Cambridge University Press, 2022)
Searching for Trust explores the intersection of trust, disinformation, and blockchain technology in an age of heightened institutional and epistemic mistrust. It adopts a unique archival theoretic lens to delve into how computational information processing has gradually supplanted traditional record keeping, putting at risk a centuries-old tradition of the 'moral defense of the record' and replacing it with a dominant ethos of information-processing efficiency. The author argues that focusing on information-processing efficiency over the defense of records against manipulation and corruption (the ancient task of the recordkeeper) has contributed to a diminution of the trustworthiness of information and a rise of disinformation, with attendant destabilization of the epistemic trust fabric of societies. Readers are asked to consider the potential and limitations of blockchains as the technological embodiment of the moral defense of the record and as means to restoring societal trust in an age of disinformation.